Education Financing in Realizing Quality Education - Febrianti, Helsi; Aulia, Yenni; Yolanda, Septiara; Yahya, Yahya (Postgraduate School, Universitas Negeri Padang, 2023)
A key factor in the development of excellent human resources is education. Education is a long-term investment that will have an economic and social impact on society. Therefore, people's interest in education always increases every year. Education financing standards and educational quality improvement go hand in hand. Education financing is a source of funds that are managed to finance learning activities and the implementation of education in schools. As a developing nation, Indonesia's biggest issue with education at the moment is its high cost, which prevents members of the lower classes from accessing it. Of course, schools will charge the highest fees to raise and sustain educational standards, so some people say that quality education is expensive. As a result, poor people's access to quality education is limited and society is increasingly divided based on social status. In this study, researchers used the way of doing a library or literary search. To get the essential information for this literature study, pertinent sources were read. Based on the issues that arise, financing for education must be carried out in line with current rules and regulations while adhering to the principles of accountability and openness. In an attempt to raise the caliber of education, this is done to boost the legitimacy of schools and madrasas. Numerous research has demonstrated that school finance affects educational quality. To raise the standard of instruction, education financing and funding is the most important thing, as can be seen from the standards governing all education unit management funds by applicable regulations. There are three types of costs in education financing standards, including a) educational unit investment costs, b) personal costs, and c) educational unit operating costs.